Uso da sílica coloidal equina no processo de congelação do sêmen canino - ROSA, Amarildo A. M. (2018)
The objective of this study was to evaluate the influence of the use of single-layer colloidal silica of glycidoxypropyltrimethoxysilane-equine formulation-Androcoll-E® (Minitube, Germany) on the freezing of canine semen. For this, 5 dogs, of different breeds, with satisfactory semen characteristics (CBRA, 2013) were used. Seven ejaculates / animal were collected and subdivided, forming: Group A - samples centrifuged at 300g for 10 minutes using Androcoll-E® and group E samples centrifuged at 700g for 10 minutes using CaniPlus Enhance® medium (Minitube; Germany). In both groups, the steps of discarding the supernatant, resuspension of the pellet in CaniPlus Enhance® (1mL of medium / 100 x 106 spermatozoa), packaging (25 x 106 spermatozoa / pallet), refrigeration (2 to 6ºC for 2 hours) , freezing (20 minutes at 5cm over N2 vapor and storage at -196C in N2 canister) and thawing (at 37 ° C for 60 seconds). After 7 days, the samples were resubmitted to centrifugation, forming 4 subgroups (16 straws / animal / subgroup): AA (Androcoll-E® centrifugation in the pre- and post-thawing stage), AE (Androcoll-E® centrifugation at pre-freezing stage and CaniPlus Enhance® in post-thawing), EA (CaniPlus Enhance® centrifugation in pre-freezing and with Androcoll-E® after thawing) and EE (CaniPlus Enhance® centrifugation in pre and post-thaw stages). Microscopic analysis of semen (concentration, vigor, membrane integrity, sperm morphology, subjective and computerized motility) was performed. Test of variance, Tukey and Kruskall Wallis were used, considering p <0.05. There was a statistical difference in relation to computerized motility and sperm morphology. The mean trajectory velocity and curvilinear velocity were higher in the EE group, the cross flagellar beating and the rectilinearity in the EA group and the linearity in the AA group. In relation to sperm morphology, the EA group presented the highest percentage of morphologically intact cells (95%), whereas in the AE group, minor defects (23%) and higher were greater than acceptable (12%). The use of equine colloidal silica after thawing (EA group) selects morphologically intact spermatozoa, which present parameters that indicate a better migration capacity and penetration into the cervical mucus.